An Alternative Numerical Model for Investigating Three- Dimensional Steam Turbine Exhaust Hood - S. Sadasivan; S. K. Arumugam; M. C. Aggarwal (Journal of Applied Fluid Mechanics, 2020)
A proper design of exhaust hood geometry is very much essential in order to improve the overall efficiency of the steam turbine plant. The geometry of the non-axisymmetric exhaust hood makes the fluid flow at the exit of the steam turbine to be radially and circumferentially non-uniform. This work involves computational simulation of steam turbine asymmetric exhaust hood flows by incorporating the actuator-disc concept. The ANSYS FLUENT, finite volume based CFD solver is used for the present computational study. In the present simulation, the implementation of actuator disc boundary conditions with and without tip leakage is described in detail. The Actuator disc model approach exhibits a similar steam turbine exhaust hood flow asymmetry and static pressure recovery compared with the results reported in the literature, highlighting the applicability of the present model in coupling the rotor tip leakage jet with the steam turbine hood flow structure with less computational effort.